EFFECIENCY MARKET HYPOTHESIS - Syarifuddin (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
In trading activities in the capital market, information is an important factor for market participants to know. Information about the capital market relates to the decisions made by investors to choose an efficient investment portfolio. The success of a company is seen from its full value. In companies that go public, the value of this company can be seen from its share price. The stock price reflects the value of the company when the capital market is efficient. An efficient market can show stock prices that fully reflect available information, this information can be in the form of company annual reports, dividends, stock splits, reports from capital market analysts, and so on. Capital market in an Islamic framework must be in accordance with sharia principles which definitely promote correct information so as to provide good to investors. Keywords: , ,